Severe Esophagitis and Chemical Pneumonitis as a Consequence of Dilute Benzalkonium Chloride Ingestion: A Case Report - Kumar, Amit; Chetiwal, Rajesh; Rastogi, Priyank; Tanwar, Shweta; Gupta, Saurabh; Patnaik, Rajesh; Vankayalapati, Maduri; Gupta, Sudhish; Arya, Alok (International Journal of Medical Students, 2021)
Background: Benzalkonium chloride (BAC) has been used as an active ingredient in a wide variety of compounds such as surface disinfectants, floor cleaners, pharmaceutical products and sanitizers. Solutions containing <10% concentration of BACs typically do not cause serious injury. As the available data regarding acute BAC toxicity is limited, we report a case of dilute benzalkonium chloride ingestion resulting in bilateral chemical pneumonitis and significant gastrointestinal injury requiring mechanical ventilatory support. The Case: A 42-year-old male presented with chief complaints of nausea, vomiting and excessive amount of blood- mixed oral secretions after accidental ingestion of approximately 100ml of BAC solution (<10%). Later he developed respiratory distress with falling oxygen saturation for which he was intubated and mechanical ventilatory support was administered. Computed tomography (CT) chest was suggestive of bilateral chemical pneumonitis and upper gastrointestinal (GI) endoscopy revealed diffuse esophageal ulcerations. The patient was managed with intravenous fluids, corticosteroids, proton pump inhibitor, empiric antibiotics and total parenteral nutrition. Conclusion: The present case report emphasizes that dilute BAC compounds can cause severe respiratory and gastrointestinal injuries. Immediate and aggressive medical treatment is crucial for improving patient outcomes and reducing the complication rates.